Knowledge of tooth avulsion first aid management among parents residing in UAE - Afraa Hussain; Raghad Hashim; Aisha Khamees (Universidade Estadual de Campinas, 2020)
Aim: This study aimed to evaluate the knowledge of parents visiting a specialized dental center in Ajman on permanent tooth avulsion and the required first aid procedure to achieve better prognoses. Methods: A cross-sectional study was conducted in Ajman Emirate, UAE. Three hundred eighty-eight parents from three nationalities (Emirati, Egyptian and Indian) residing in UAE answered a constructed questionnaire that included demographic information related to the participants and questions related to permanent tooth avulsion and the required first steps for its management. Results: Study findings reflect deficiencies in the following areas. Of the 388 parents, (236, 60.8%) had poor knowledge about permanent tooth avulsion. Parents who had previous knowledge obtained information from unsupported sources, such as friends (145, 37.4%). Out of 388 parents, (324, and 83.5%) would not replant the tooth. Finally, the majority of the participants did not know the proper media to store the avulsed permanent tooth with one-third of parents choosing cotton or water (142, 36.6%). Conclusion: This study showed a lack of knowledge regarding permanent tooth avulsion among parents from the major nationalities residing in UAE. However, the respondents represent major differences regarding related to knowledge, replant, and storage of avulsed permanent teeth.